2016
DOI: 10.1161/jaha.116.003891
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Signature of Remote Ischemic Preconditioning Involving a Cocktail of Amino Acids and Biogenic Amines

Abstract: BackgroundRemote ischemic preconditioning (RIPC) is an attractive therapeutic procedure for protecting the heart against ischemia/reperfusion injury. Despite evidence of humoral mediators transported through the circulation playing a critical role, their actual identities so far remain unknown. We sought to identify plasmatic RIPC‐induced metabolites that may play a role.Methods and ResultsRat plasma samples from RIPC and control groups were analyzed using a targeted metabolomic approach aimed at measuring 188… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 57 publications
2
47
0
Order By: Relevance
“…This is superficially surprising given its well-understood role as an oxygen-sensing enzyme as opposed to one with significant roles in metabolic flux. Some support for a role for the kynurenine pathway in the mechanism of RIPC has been provided by studies in humans and rats in which circulating metabolites, including kynurenine and glycine, that demonstrated elevated levels after RIPC were injected prior to myocardial infarction and had a protective effect 32 .…”
Section: Is There a Role For Kynurenic Acid As The Mediator Of Remotementioning
confidence: 99%
“…This is superficially surprising given its well-understood role as an oxygen-sensing enzyme as opposed to one with significant roles in metabolic flux. Some support for a role for the kynurenine pathway in the mechanism of RIPC has been provided by studies in humans and rats in which circulating metabolites, including kynurenine and glycine, that demonstrated elevated levels after RIPC were injected prior to myocardial infarction and had a protective effect 32 .…”
Section: Is There a Role For Kynurenic Acid As The Mediator Of Remotementioning
confidence: 99%
“…Analysis of the concentrations of metabolites in plasma samples of patients subjected to RIC revealed an increase in glycine concentration following RIC [ 23 ]. This is relevant to the current review, as glycine is known to be an inhibitory neurotransmitter in the central nervous system, and specifically, in parasympathetic nuclei [ 22 , 131 , 132 ].…”
Section: The Mechanisms Of Cardioprotection By Remote Ischaemic Condimentioning
confidence: 99%
“…This is relevant to the current review, as glycine is known to be an inhibitory neurotransmitter in the central nervous system, and specifically, in parasympathetic nuclei [ 22 , 131 , 132 ]. In the above-mentioned study, the injection of glycine mimicked the protective effects of RIC in rats [ 23 ]. García-Dorado’s group demonstrated that glycine exerts cross-species cardioprotection against infarction through glycine receptor activation [ 66 ].…”
Section: The Mechanisms Of Cardioprotection By Remote Ischaemic Condimentioning
confidence: 99%
“…At present, there are three theories: the humoural, the neural, and the systemic [15]. The largest body of preclinical data supports the concept of an RIPCinduced factor(s) in the bloodstream that conveys protection from the transiently ischemic limb to the remote organ(s) [16][17][18][19][20][21][22]. Moreover, the preconditioning protection has been shown to be transferable with the plasma, even in cases of cross-species transfer [17,18,23,24] and it appeared to be mediated via a small, unknown hydrophobic factor under 30 kDa [17,25].…”
Section: Introductionmentioning
confidence: 99%